Adults with dyslexia demonstrate attentional orienting deficits. - Buchholz, J; Aimola Davies, A (2008)
Alerting, orienting and executive control of attention are investigated in five adult cases of dyslexia. In comparison with a control group, alerting and executive control were found to be generally intact for each case. Two spatial cueing tasks were employed. For the task requiring target detection, orienting difficulties were evident only in peripheral locations. While orienting attention to parafoveal stimuli was intact for this detection task, it was found to be impaired for the discrimination task. These results are discussed with respect to the methodological differences of the two tasks. It is suggested that the observed orienting deficit may be specific to adjusting the size of attentional focus in individuals with dyslexia, and that this could contribute to the reading difficulties observed.